Irradiated films via nuclear technology for food packaging purposes - Nur Sara Syuhada, Baharudin (2014)
The application of radiation towards the polymer modification seems to be beneficial as polymers play an important role in our daily life. At this moment, there is about 200 million tonnes of plastics consumption globally, with an approximation growth of 5% per annum. The increasing amount of synthetic plastics packaging films has led to a serious ecological problem due to its non-biodegradability properties. Therefore, this research is to produce different formulations of biodegradable irradiated antimicrobial starch films with different amount of dosage, where several characteristics of the films were tested. The characterization includes ‘Absorption Test’, ‘Gel Content Test’, ‘Conductivity Test’, ‘Soil Burial’, and ‘Scanning Electron Microscopy’. From the results obtained, the highest dosage of radiation seems to be the best condition in producing the biodegradable films. This is because, the highest dosage, which is at 30kGy, results in the lowest amount of water absorption (%), lowest amount of conductivity, as well as the highest amount of gel content (%). The application of radiation process on the production of biodegradable films seems to be a good potential solution in substituting the synthetic plastics for a better future